Hesperus rougemonti sp. n. (Coleoptera, Staphylinidae) from Borneo - Schillhammer, Harald (Zootaxa, 2016)
The genus Hesperus Fauvel is, in its current concept, an obviously polyphyletic assemblage. One of the species groups that stand out, due to a combination of characters unusual for Hesperus, is the borneensis group. These characters are the subserrate antennae and the paramere bearing numerous peg setae. Otherwise, the members of this group look as typical for a Hesperus as it can be. At present, the group comprises the following species: H. birmanus Cameron, 1932, H. borneensis Bernhauer, 1915, H. javanus Cameron, 1937, H. malayanus Cameron, 1932a, H. susannekontrusae Schillhammer, 2005, H. temburong Schillhammer, 2002, H. watanabei Shibata, 2002, and H. wemmeri Schillhammer, 2002.